The severity of hereditary porphyria is modulated by the porphyrin exporter and Lan antigen ABCB6 - Yu Fukuda (Nature Portfolio, 2016)
Accumulation of intermediates of haem biosynthesis, porphyrins, is harmful and usually inherited, but it is unclear how the same mutation may make some individuals more ill than others. Here, the authors show that a porphyrin transporter ABCB6 is a modulator of porphyria, and that patients with functionally defective ABCB6 show more severe symptoms.